Mud, Microbes, and Macrofauna: Seasonal Dynamics of the Iron Biogeochemical Cycle in an Intertidal Mudflat - Beam, Jacob P.; George, Sarabeth; Record, Nicholas R.; Countway, Peter D.; Johnston, David T.; Girguis, Peter R.; Emerson, David (Frontiers in Marine Science, 2020)
Microorganisms and burrowing animals exert a pronounced impact on the cycling of redox sensitive metals in coastal sediments. We hypothesized that the iron biogeochemical cycle and associated sedimentary microbial community will respond to seasonal changes in a bioturbated intertidal mudflat. In this study, we monitored the spatiotemporal dynamics of porewater and highly reactive solid phase iron with the corresponding prokaryotic and eukaryotic sedimentary microbial communities over one annual cycle from November 2015 to November 2016. Continuous and seasonally variable pools of both porewater Fe(II) and highly reactive iron (FeHR) were observed throughout the seasons with significant increases of Fe(II) and FeHR in response to increased sediment temperature in summer months. Maximum concentrations of Fe(II) and FeHR were predominantly confined to the upper 5 cm of sediment throughout the year. Iron-oxidizing and -reducing microorganisms were present and stable temporally, and exhibited a depth-dependent stratification likely due to availability of Fe(II) and FeHR pools, respectively. Zetaproteobacteria, presumptive lithotrophic iron-oxidizing bacteria, were present at abundances around 0.5–1% in the top 5 cm of sediment with decline abundance with depth. As a whole the microbial community was relatively stable across the seasons, and showed strongest separation with depth, probably driven by changes in oxygen availability and organic matter. The Deltaproteobacteria, principally taxa known to be associated with sulfur and iron cycling, were prevalent, especially at >5 cm depth. Gammaproteobacteria and Bacteroidetes were also abundant, with putatively aerobic members especially prevalent in the cm of the sediment. The relative abundance of diatoms, estimated from abundance of 18S rRNA gene counts, showed evidence of a seasonal signal possibly tied to spring and fall blooms. Overall, analysis of phytoplankton found significant abundance at depth, likely due to the feeding and bio-mixing activity of marine worms. Macro-, and meiofauna, consistent with expected taxa, were detected throughout the year via 18S gene counts, and showed some seasonal variations that may influence sedimentary iron transformations by active microbial grazing. In summary, this analysis revealed relatively consistent temporal and spatial trends in iron geochemistry and microbial and macrobial community composition, while also indicating a complex dynamic of microbial and macrobial interactions are responsible for maintaining these processes.